2004
DOI: 10.1242/jcs.00971
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin-10, a KiSS-1/metastin-derived decapeptide, is a physiological invasion inhibitor of primary human trophoblasts

Abstract: Trophoblast invasion of the uterine extracellular matrix, a critical process of human implantation and essential for fetal development, is a striking example of controlled invasiveness. To identify molecules that regulate trophoblast invasion, mRNA signatures of trophoblast cells isolated from first trimester (high invasiveness) and term placentae (no/low invasiveness) were compared using U95A GeneChip microarrays yielding 220 invasion/migrationrelated genes. In this 'invasion cluster', KiSS-1 and its G-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
359
1
33

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 332 publications
(409 citation statements)
references
References 43 publications
16
359
1
33
Order By: Relevance
“…These included members of the growth hormone gene cluster, namely CSH1 and GH2 (Chen et al, 1989), and genes involved in fetal or placental development, namely KISS1 and ADAM12 (Shi et al, 2000;Bilban et al, 2004). We first validated whether the four transcripts were detectable in maternal plasma and pregnancy-specific.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included members of the growth hormone gene cluster, namely CSH1 and GH2 (Chen et al, 1989), and genes involved in fetal or placental development, namely KISS1 and ADAM12 (Shi et al, 2000;Bilban et al, 2004). We first validated whether the four transcripts were detectable in maternal plasma and pregnancy-specific.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, some of the genes on the list, including CSH1 (chorionic somatomammotropin hormone 1 (placental lactogen)), GH2 (growth hormone 2 (placental growth hormone)), KISS1 (KiSS-1 metastasissuppressor), and ADAM12 (ADAM metallopeptidase domain 12 ) are functionally related to fetal or placental development (Shi et al, 2000;Gluckman andCopyright  2009 John Wiley &Sons, Ltd. Pinal, 2003;Bilban et al, 2004). Hence, in this study, we explored whether these placental-derived transcripts could serve as new maternal plasma RNA markers that could be used to monitor fetal growth or give us a better understanding of IUGR pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…The actions of the KP peptides in the neuronal cell systems do not appear to be mediated via activation of either the GPR-54 or NPFF receptor systems that are known targets of KP. 6,7,10,11 Compounds that bind to amyloid peptides are also likely to modify Congo red binding, 54 and the KP peptides shared this property. Congo red binding is suggestive of fibril formation, 19 and the ability of KP peptides to inhibit this suggests that there is potential inhibition of amyloid aggregation.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…6,7 Biological activity of KP peptides requires the KP 45−54 sequence and is mediated via a specific KP receptor (GPR-54). 6,7 Lack of KP signaling via the GPR-54 receptor is associated with reproductive system failure. 8 Cleavage of the KP 45−54 peptide between residues 51 and 52 by matrix metalloproteinases abolishes the activation of GPR-54 by the KP 45−54 peptide.…”
mentioning
confidence: 99%
“…The KiSS-1 gene belongs to a larger family of RFamide (Arg-Phe-NH2) peptide ligand that can activate the human ortholog (hOT7T175 or AXOR12) of GPR54, also termed as KiSS-1 gene plays a major role in regulation of hypothalamic pituitary gonadal (HPG) axis via regulating the secretion of gonadotropin releasing hormone (GnRH) in the hypothalamus. The greatest peripheral source of KPs in the human is placenta and KiSS-1 is located within the syncytiotrophoblast cells (Bilban et al, 2004). Studies on functional analysis have demonstrated the fundamental role of KiSS-1 in multiple process include i.e.…”
Section: Discovery Of Kisspeptins and Kiss-1mentioning
confidence: 99%